(untitled) (Literary Voice, 2025)
This research paper is meant to be an extension of any study of Women’s Studies. The roles of women in societies and domains of knowledge are not devoid of struggles of varied hues. Despite the struggles, women have spelled out a strong presence for themselves over centuries. In the realm of Women’s Studies, the waves of Feminism and Womanism have rendered immense strengths and conviction to makeovers in policies, attitudes and structures by highlighting and resisting injustices targeted towards women and men. The struggles and resistances have been strengthened by the collective powers of women’s organisations and women’s’ influences on drafting better political and social policies that reduce the struggles and sufferings of both, men and women. This paper elaborates the concept and role of Sisterhood and its fundamental status in the realm of Women’s Studies.